Endothelial protective effect of pitavastatin - A. S. Berns; V. V. Kashtalap (Кардиоваскулярная терапия и профилактика, 2023)
The article discusses topical issues of modern concepts of aging, including vascular aging due to the progression of endothelial dysfunction, atherogenesis, chronic and acute cardiovascular atherosclerosis-related diseases. Modern potential of anti-aging therapy aimed at slowing the progression of vascular aging and endothelial dysfunction are reflected. A descriptive literature review was carried out based on the analysis of sources from the PubMed, eLibrary databases for the following keywords: endothelium, aging, pitavastatin, anti-aging effect (endothelium, aging, pitavastatin, anti-aging effect). Based on a review, the role of pitavastatin is shown not only as an effective cholesterol-lowering drug, but also as an agent with a large number of proven pleiotropic effects, as well as an optimal safety profile and a low risk of side effects and drug interactions. On the example of a case, the potential of high-intensity lipid-lowering therapy with the use of pitavastatin in a comorbid patient are illustrated.